SISTEMATIK LITERATUR REVIEW: LITERASI SAINS DAN SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) - Khaerun Nisa; Wiyanto Wiyanto; Woro Sumarni (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
AbstractPISA test results show that scientific literacy for many countries around the world is categorized as low. SETS is one approach that can improve scientific literacy. However, research for the combination of these two topics is still challenging to find. This article aims to systematically show the scope of scientific literacy research and SETS from 2016-2020. This study uses the SLR (Systematic Literature Review) method that adopts the PRISMA systematic. The study population consisted of all articles on JRST, IJSE, SE, and JPCS and other journals from the ERIC, DOAJ, and Science Direct directories. The sample of this research is 44 articles obtained in these journals. The results of the article analysis show that JPCS, IJERE, and IJSE publish the articles with the highest quantity, where the topic of scientific literacy is the topic with the highest quantity and the combined topic of scientific literacy SETS is the topic with the least quantity. The sub-topic of scientific literacy and SETS articles most studied was the development of learning books related to scientific literacy and SETS. Most of the types of research used are empirical research types. Further research is suggested to look at the effect of SETS on scientific literacy or develop a SETS-based learning media and student learning environment in improving scientific literacy.AbstrakHasil tes PISA menunjukan literasi sains untuk banyak negera di seluruh dunia dikategorikan rendah. SETS menjadi salah satu pendekatan yang dapat meningkatkan literasi sains. Namun, penelitian untuk gabungan kedua topik ini masih sulit ditemukan. Artikel ini bertujuan untuk menunjukan sistematik cakupan penelitian literasi sains dan SETS dari tahun 2016-2020. Penelitian ini menggunakan metode SLR (Systematic Literature Review) yang mengadopsi sistematik PRISMA. Populasi penelitian terdiri atas seluruh artikel pada JRST, IJSE, SE, dan JPCS, serta pada jurnal lainnya dari direktori ERIC, DOAJ, dan Science Direct. Sampel penelitian ini adalah 44 artikel yang diperoleh pada jurnal-jurnal tersebut. Hasil analisis artikel menunjukan JPCS, IJERE dan IJSE menerbitkan artikel dengan kuantitas terbanyak, di mana topik literasi sains menjadi topik yang kuantitas paling banyak dan topik gabungan literasi sains dan SETS menjadi topik yang kuantitas paling sedikit. Sub-topik artikel literasi sains dan SETS yang paling banyak diteliti adalah pengembangan buku pembelajaran terkait literasi sains dan SETS. Sebagian besar tipe penelitian yang digunakan ialah tipe penelitian empiris. Penelitian lebih lanjut disarankan yaitu melihat pengaruh SETS terhadap literasi sains atau mengembangkan sebuah media pembelajaran berbasis SETS dan lingkungan belajar siswa dalam meningkatkan literasi sains.